Peranan Paguyuban Maha Gotra Pasek Sanak Sapta Rsi (MGPSSR) dalam Peningkatan Kualitas Calon Diksita di Kota Denpasar - Ambarnuari, Mery; Gaduh, Acyutananda Wayan; Setyawan, I Putu Adi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
This research explores the role of the Maha Gotra Pasek Sanak Sapta Rsi Association (MGPSSR) in efforts to improve the quality of Diksita candidates in Denpasar City. Based on the theories of Structuration and Structural Functionalism, this research examines the historical traces of the Maha Gotra Pasek Sanak Sapta Rsi, their role in developing prospective Hindu religious leaders, especially Diksita or sulinggih candidates who previously had to go through pinandita/pemangku or sarati banten training, and the impact that occurred due to their role. carried out by Maha Gotra Pasek Sanak Saptra Rsi. Data was obtained through in-depth interviews using snowball sampling techniques. The findings show that Maha Gotra Pasek Sanak Sapta Rsi plays an important role in increasing the understanding of prospective diksita in the city of Denpasar regarding Hindu religious teachings as well as having an understanding and ability in practicing religious rituals. The significant impact that Diksita candidates can feel can be seen in the spiritual and intellectual qualities of Diksita candidates in Denpasar. MGPSSR's role in developing Diksita candidates not only improves individual spiritual qualities, but also has a wider impact on the Hindu community in Bali. Through the training program they manage, MGPSSR is able to produce quality religious leaders, who are able to lead people in various aspects of religious life. This program is also a model for other communities in Bali who want to improve the quality of prospective religious leaders in their communities. Keywords: MGPSSR, Diksita, Paguyuban, Hindu Religion